The quantitative study of serial murder: Regression is not transgression. (January 2019) - Fridel, Emma E.; Fox, James Alan
Abstract: In Too Few Victims: Finding the Optimal Minimum Victim Threshold for Defining Serial Murder, we empirically examined how victim count influences the definition of serial homicide. With a series of multinomial logistic regressions, we determined that a cutoff of three victims was optimal to ensure a more homogeneous population, and recommended a return to this traditional threshold (Fridel & Fox, 2018). In response, Yaksic (2018) published a scathing review of our work, claiming that our study was "transgressing" against serial homicide research and actively hampering law enforcement investigations. In addition to defending our original study, we reject his suggestion to rely solely on the qualitative methods of the past and firmly advocate for the modernization of serial homicide research through rigorous quantitative analysis.